1950
DOI: 10.1002/ar.1091080205
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian origin of bronchial arteries

Abstract: The variability of the bronchi a1 arteries is mentioned by a iimnber of writws but details of the topography of these nriations are difficult to come by, although "Bnowledge of their variable origins a i d distribution would provide a practical addition to the operator's armamentarium" (Ci~dcJ\\~ell ct a]., '48). 1)ESCRJPTION O F CASENale dissecting room body, aet. 66; ccrtified cause of death:arteriosclerosis. The right and left bronchial arteries originated from a single stem which arose in common with the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1963
1963
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…O'Rahilly, Debson, and King (1950) could only find 12 cases to add to their one, though in a series of 150 necropsies, Cauldwell et al (1948) found an incidence of 2 per cent. In association with pulmonary atresia, 3 further cases have been recorded (Allanby et al, 1950;Campbell and Gardner, 1950;Lamers and Bruins, 1958).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…O'Rahilly, Debson, and King (1950) could only find 12 cases to add to their one, though in a series of 150 necropsies, Cauldwell et al (1948) found an incidence of 2 per cent. In association with pulmonary atresia, 3 further cases have been recorded (Allanby et al, 1950;Campbell and Gardner, 1950;Lamers and Bruins, 1958).…”
Section: Discussionmentioning
confidence: 96%
“…The bronchial artery from the right subclavian to the right upper and middle lobes had an origin, course, and distribution similar to that described by Cauldwell et al (1948), though no middle lobe branch was described in their case. O'Rahilly et al (1950) described a bronchial artery arising from the left subclavian and supplying the lower lobes of both lungs, passing anterior to the carina and entering the right lower lobe on the antero-medial aspect of the bronchus. The course of the vessel arising from the left subclavian in the present case is similar to this, apart from the absence of a branch to the left lung.…”
Section: Discussionmentioning
confidence: 99%
“…11 ' 12 In normal adults, bronchial arteries, usually two or three in number, arise mainly from the aorta, but also from the intercostal arteries. Of note, normal bronchial arteries can also originate from brachiocephalic or subclavian arteries or their branches, 13 and rarely from the coronary arteries. 11 Normal bronchial arteries may enlarge in the presence of any factor that decreases the flow of blood to the lungs, for instance in the presence of congestion, as well as in association with other forms of congenital cardiac disease.…”
Section: Embryological Aspectsmentioning
confidence: 99%
“…Without doubt, the most complex anatomic arrangements are found in patients with systemicto-pulmonary collateral arteries (Figs 9 and 10). These vessels, usually from two to six in number, 13 may vary significantly in terms of their size, origin, and connections to the lungs.…”
Section: Supply By Systemic To Pulmonary Collateral Arteriesmentioning
confidence: 99%
See 1 more Smart Citation